PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE DALAM BENTUK GOOGLE SITES UNTUK PESERTA DIDIK KELAS XI IPS - Qonita Putri Yuliananda; Norida Canda Sakti (STKIP Persada Khatulistiwa Sintang, 2022)
This research was conducted because there are limited media on complex material. The urgency of this research is how to develop technology-based modern digital learning media in the era of digitalization, modernization as well as a pandemic with the hope that the developed learning media can have a positive impact on education in the modern era, one of which is providing effective, responsive, and efficient learning media. Power point is applied to all materials that are considered complex. This method is research and development using 4D models i.e defining, designing, developing, distributing. The development of learning media aims to know the feasibility of Google Sites learning media from the aspects of material, media, media practicality, student responses, evaluations. This media is validated by a team of expert validators. This research was tested on twenty students of class 11 IPS SMA Negeri 16 Surabaya. Learning media contains 7 menus, namely instructions for use, attendance, materials, videos, evaluations, biographies. The primary data collection by interviews, questionnaires and documentation which were recapitulated and analyzed through qualitative and quantitative data analysis. The research output is learning media based on google sites website. The results of this media research validation is very feasible, and get positive respons from students